2016
DOI: 10.14311/ap.2016.56.0417
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Model of Steel Fibre Reinforced Concrete Subjected to High Temperatures

Abstract: Research on structural load-bearing systems exposed to elevated temperatures is an active topic in civil engineering. Carrying out a full-size experiment of a specimen exposed to fire is a challenging task considering not only the preparation labour but also the necessary costs. Therefore, such experiments are simulated using various software and computational models in order to predict the structural behaviour as exactly as possible. In this paper such a procedure, focusing on software simulation, is describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…For particular fibre volume ratios and compressive strengths, the formation of several cracks in the pure bending zone complicates measurement of the crack opening and hampers assessment of the deflections (Gopalaratnam 1995). Both approaches, nevertheless, are capable of predicting post-cracking behaviour of SFRC (Blesak et al 2016;Groli, Caldentey 2016;Iqbal et al 2015); however, addition of bar reinforcement complicates assessment of the residual effect of the fibres (Gribniak et al 2012;Sanchez-Aparicio et al 2015). The moment-curvature relationships of the full-scale beams are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For particular fibre volume ratios and compressive strengths, the formation of several cracks in the pure bending zone complicates measurement of the crack opening and hampers assessment of the deflections (Gopalaratnam 1995). Both approaches, nevertheless, are capable of predicting post-cracking behaviour of SFRC (Blesak et al 2016;Groli, Caldentey 2016;Iqbal et al 2015); however, addition of bar reinforcement complicates assessment of the residual effect of the fibres (Gribniak et al 2012;Sanchez-Aparicio et al 2015). The moment-curvature relationships of the full-scale beams are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical behavior of fibrous concrete after burning up to a temperature of 900 o C by Antonius et al [15] and Purwanto et al [16] proposes a constitutive equation for mechanical behavior but is however limited to the volume of the fiber fraction of 0.5%. Bezerra et al [17] and Chen et al [18] investigated the mechanical behavior of steelfibrous concrete at high temperatures where the burning temperature reached 500 o C. On the other hand, an analysis simulation of fibrous concrete based on a numerical method that was validated against experimental results and revealed that postburn fibrous concrete tends to experience a trend of decreasing strength but its ductility increases if the temperature applied is more excessive [19]. Furthermore, Bezerra et al [17] and Zhang et al [20] reveal the residual strength of steel-fibrous concrete at various temperatures is more superior than the residual strength of plain concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the properties of the burnt concrete, including the duration and the temperature of the fire are very important to recognize in order to ensure the level of security of after burnt structure. also been extensively investigated [9][10][11][12]. Similarly, the application of fibrous concrete at high temperatures has been carried out [13].…”
Section: Introductionmentioning
confidence: 99%